2022
DOI: 10.1007/s10071-022-01723-4
|View full text |Cite
|
Sign up to set email alerts
|

Testing cognitive models of decision-making: selected studies with starlings

Abstract: The behavioural sciences are home to controversies that have survived for centuries, notably about the relation between observable behaviour and theoretical constructs addressing out-of-sight processes in the agents’ brains. There is no shared definition for cognition, but the very existence of a thriving journal called Animal Cognition proves that such controversies are still live and help to (a) promote research on the complexity of processes leading to action, and (b) nudge scholars to restrict their cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Furthermore, instances of context-dependent value learning have also been observed reliably in a wide range of non-human animals, as diverse as mammals, birds and insects 38,55 . The coincidence between our present cross-cultural results and the ample array of cross-species prior findings, reinforces the notion that RL processes may be largely hard-coded and evolutionary stable 56 . Indeed, despite the incidental generation of suboptimal preferences (e.g., in the Transfer phase), context-dependent value learning likely presents an overall adaptive value.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, instances of context-dependent value learning have also been observed reliably in a wide range of non-human animals, as diverse as mammals, birds and insects 38,55 . The coincidence between our present cross-cultural results and the ample array of cross-species prior findings, reinforces the notion that RL processes may be largely hard-coded and evolutionary stable 56 . Indeed, despite the incidental generation of suboptimal preferences (e.g., in the Transfer phase), context-dependent value learning likely presents an overall adaptive value.…”
Section: Discussionsupporting
confidence: 87%
“…Previous research has shown that latencies to respond can be used as a sensitive metric of value and preference: Organisms usually respond faster to preferred than to non-preferred alternatives when presented individually (e.g., Aw et al 2012 ; Lagorio and Hackenberg 2012 ; Macías et al 2021 ; Monteiro et al 2020 ; Reboreda and Kacelnik 1991 ; Shull et al 1990 ; Vasconcelos et al 2013 ; for reviews see Kacelnik et al 2011 , 2023 ). We analyzed the latencies to respond to the initial link during forced trials in each condition in search of converging evidence regarding the effect of the long / short ratio on preference.…”
Section: Resultsmentioning
confidence: 99%
“…By dissociating the effects of the liking and wanting components of motivation, this type of analysis offers a potential way forward to a long lasting problem in insect cognitive studies (66). Standard recordings of behavioural vigour via high-speed videography (see also (98)) could thus provide an alternative, or complementary way of measuring preference between options, beyond the multi-choice trials classically used (8). Knowledge could be gained not only by examining the factors leading to a change in the flight parameters, but also by studying the rate of decline of these parameters as the expectations regarding a simple or composed (99) potential reward are altered.…”
Section: Discussionmentioning
confidence: 99%
“…the time before the subject attends to an option when presented alone). Evidence that sampling latencies inversely correlates with the level of preference has accumulated in both avian and mammalian species (7,8). This correlation has its origin in the relationship between behavioural vigour and the average reward rate of the option available (9,10).…”
Section: Introductionmentioning
confidence: 99%